Blood DNA methylation signatures to detect dementia prior to overt clinical symptoms. Issue 1 (9th July 2020) - Fransquet, Peter Daniel; Lacaze, Paul; Saffery, Richard; Phung, James; Parker, Emily; Shah, Raj; Murray, Anne; Woods, Robyn L.; Ryan, Joanne
Abstract: Introduction: This study determined whether blood DNA methylation (DNAm) patterns differentiate individuals with presymptomatic dementia compared to controls. Methods: DNAm was measured in 73 individuals prior to dementia diagnosis and 87 cognitively healthy controls matched for age, sex, smoking, education, and baseline cognition. DNAm was also measured at 3 years follow‐up in 25 dementia cases, and 24 controls. Results: Cases and controls differed in DNAm (unadjusted P < .01) at the time of diagnosis (n = 28, 787 probes), and pre‐diagnosis (n = 15, 111 probes), with cg01404610 ( General transcription factor IIA subunit 1 gene) significant after correction for multiple testing. Overall, 1150 probes overlapped between analyses (methylation differences from –10.6% to +11.0%), and effect sizes increased from pre‐diagnosis to diagnosis. Discussion: Discernible blood DNAm signatures are in dementia cases before the appearance of overt clinical symptoms. Blood‐based methylation may serve as a potential biomarker of dementia, but further investigation is needed to determine their true clinical utility.